Electrical Resistivity of Fullerenes at High Pressures - Núñez Regueiro, M.; Bethoux, O.; Mignot, J.-M.; Monceau, P.; Bernier, P.; Fabre, C.; Rassat, A. (IOP Publishing, 1993)
Fil: Núñez Regueiro, M. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina; Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina; Centre National de la Recherche Scientifique; Francia